DIDATTICA DEL LESSICO: UN PERCORSO BIBLIOGRAFICO (ItalianoLinguadue, 2025)
Lexical education: a bibliographical pathwayThis contribution presents a structured approach to the study of vocabulary didactics, highlighting the growing body of literature on the topic over recent decades. Recognizing the necessity for a more organized framework that aids educators and researchers in navigating the subject, we adopt a classification system inspired by Barni, Troncarelli, and Bagna (2008). The division consists of three main categories: 1. General Issues and Lexical Analysis Models: This first class encompasses works that address broad themes and various models for analyzing vocabulary. These contributions are particularly relevant for applications in the teaching and learning of both first (L1) and additional languages (L2). 2. Corpus Linguistics and Lexical Tools: The second category includes publications focused on corpus linguistics and the resources available for describing the lexical system, such as dictionaries. 3. Didactic Techniques and Classroom Experiences: The third class is dedicated to articles that propose teaching techniques, experimental didactic strategies, and accounts of classroom practices. These contributions offer practical insights and methodologies that educators can apply in their teaching. To ensure a thematic and chronological coherence, we have curated a selection of studies that are representative rather than exhaustive, spotlighting key research from the 1970s to the early 2000s, as well as more recent developments from 2019 onwards. This structured overview aims to facilitate a clearer understanding of the didactics of vocabulary, making it more accessible for teachers and scholars alike.